1988
DOI: 10.1149/1.2096227
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3‐methylthiophene): A Stable Cathode‐Active Material for Secondary Batteries

Abstract: The electrical properties of poly(3‐methylthiophene) (P3MT) films synthesized by electrochemical polymerization and the discharge characteristics of secondary batteries utilizing P3MT film as the cathode‐active material are described. The P3MT was synthesized in film forms by electrochemical polymerization in the propylene carbonate solutions containing LiBF4 or LiAsF6 . The conductivity of the AsF6− doped [30 mole percent (m/o)] P3MT film prepared at 25°C was about 200 S/cm. A P3MT/LiBF4+PC+EC/normalAl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…114 polymerised to structures sustaining a stable doping up to 0.38 (e − /MU), corresponding to almost 100 mAh/g in a lithium cell. 118 It was in fact demonstrated that a sharp conductivity maximum existed for films produced with a current density of 10 mA/cm, where a granular structure develops. This is the preferred structure for high performance of the films.…”
Section: Conducting Polymer Filmsmentioning
confidence: 99%
“…114 polymerised to structures sustaining a stable doping up to 0.38 (e − /MU), corresponding to almost 100 mAh/g in a lithium cell. 118 It was in fact demonstrated that a sharp conductivity maximum existed for films produced with a current density of 10 mA/cm, where a granular structure develops. This is the preferred structure for high performance of the films.…”
Section: Conducting Polymer Filmsmentioning
confidence: 99%
“…Complexation of zinc was accounted for by utilizing a speciation analysis based on an ideal solution of hydrated halocomplexes according to Jacobsen and Skou (5,6). Complexation of zinc was accounted for by utilizing a speciation analysis based on an ideal solution of hydrated halocomplexes according to Jacobsen and Skou (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…We used poly 3-methylthiophene (PMT), reportedly having an electrical conductivity in the range of 10 to 2 • 103 S cm -1 in the doped state (3)(4)(5). One alternative to carbon was to use electrically conducting polymers fabricated as extremely thin films with high surface area.…”
mentioning
confidence: 99%
“…8). (Aa/Ar [12] where A~ is the area of passive metal and ia(E) is the galvanic (anodic) current density on the passive metal (typically about 0.2 ~A/cm 2 on Ti). The first term in parenthesis is due to 'chemical degradation,' and the second term is the result of galvanic current between the polymer film and the passive metal.…”
Section: De/dt = (De/dq) (Dq/dt) = (De/dq) (-Kq 2)mentioning
confidence: 99%
“…The first term in parenthesis is due to 'chemical degradation,' and the second term is the result of galvanic current between the polymer film and the passive metal. [12] using experimentally measured i~(E) and compared to experimental data for a P(3-MT) film coupled to Ti electrodes of different siZe. [4] into Eq.…”
Section: De/dt = (De/dq) (Dq/dt) = (De/dq) (-Kq 2)mentioning
confidence: 99%